Bottom‐up topography assembly into 3D porous scaffold to mediate cell activities. Issue 6 (26th May 2015) - Cheng, Delin; Hou, Jie; Hao, Lijing; Cao, Xiaodong; Gao, Huichang; Fu, Xiaoling; Wang, Yingjun
Abstract: Native cells live in a three‐dimensional (3D) extracellular matrix (ECM) capable of regulating cell activities through various physical and chemical factors. Designed topographies have been well proven to trigger significant difference in cell behaviours. However, present topographies are almost all constructed on two‐dimensional (2D) substrates like discs and films, which are far from features like 3D and porosity required in application like bone repair. Here we bottom‐up assembled poly(lactic‐ co ‐glycolic acid)/calcium carbonate (PLGA/CC) microspheres with superficial porous topography intactly into a 3D porous scaffold. Because the scaffold was obtained through a mild technique, the bioactivity of released BMP‐2 was well retained. Mouse bone marrow mesenchymal stem cells (mMSCs) were cultured on produced scaffolds having different 3D topographies. It turned out that osteogenic differentiation of mMSCs did respond to the 3D topographies, while proliferation didn't. Gene expression of αv and β1 integrins revealed that adhesion was supposed to be the underlying mechanism for osteogenic response. The study provides insight into enhancing function of practical scaffolds by elaborate topography design. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1056–1063, 2016.